Implementasi Pembiasaan Shalat Berjama’ah dalam Membentuk Karakter Disiplin Siswa di MTs Negeri 9 Blitar - Muhammad Nurmala Majid; Mochamad Nasichin Al Muiz (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This research is motivated by the low discipline of a number of students in performing congregational prayers, which is indicated by lateness, disorderliness, and efforts to avoid the obligation. The purpose of this study was to determine the urgency, implementation strategies, and supporting and inhibiting factors for the habit of congregational prayers in forming the character of student discipline at MTsN 9 Blitar. This study uses a qualitative approach with a case study type. Data collection techniques were carried out through interviews, observations, and documentation, while data analysis was through reduction, presentation, and drawing conclusions, with data validity obtained through triangulation, observer persistence, and peer discussion. The results of the study showed that the habit of congregational prayers has a high urgency in forming the character of student discipline, because it fosters an orderly, punctual, and consistent attitude towards obligations. The strategies used include habituation, role models, supervision, and punishment. Supporting factors consist of adequate facilities, educator commitment, and clear regulations, while inhibiting factors include lack of parental support, low student awareness, and the location of the mosque outside the madrasah environment. This habituation has positive implications in instilling the value of discipline through a religious approach in the educational environment.